Jurdical Review of Defaults in Debt and Receivable Agreements - Simbolon, Dian Lorenjaya; Siallagan, Haposan; Situmorang, Samuel (Greenation International Journal of Law and Social Sciences, 2024)
Breach of contract is an act that harms the other party in various types of agreements, including loan agreements, leading to both material and immaterial losses for the agreed party. Therefore, this journal will examine the legal aspects of breach of contract in loan agreements through a study of Decision Number 686/Pdt.G/2021/Pn Mdn. The analysis focuses on two main research questions: first, the legal consequences arising from breach of contract in this loan agreement; and second, the basis for the judge's reasoning in issuing Decision Number 686/Pdt.G/2021/Pn Mdn. Using a normative approach, this research analyzes the decision based on relevant legislation and jurisprudence. The research findings are expected to provide a deeper understanding of the legal implications of breach of contract in Indonesian judicial practice, particularly regarding loan disputes, and contribute to an understanding of the judge's reasoning process in similar cases.